Potassium - modulated photosynthetic performance of mango plants infected by Ceratocystis fimbriata - Cacique, Isaias Severino (2014)
The mango wilt, caused by the fungus Ceratocystis fimbriata, is one of the most important diseases affecting mango production. Considering the beneficial effects provided by the potassium (K) supply in other profitable crops and the lack of information on the effect of macronutrients in the development of the mango wilt, the present study aimed to evaluate how plants respond physiologically to the infection caused by C. fimbriata. Plants were grown in plastic pots containing 58 or 240 mg K dm -3 in the substrate. Disease symptoms were more pronounced in plants inoculated and supplied with the lower K rate, reaching higher values for the disease indices URLL (upward relative lesion length) 79%, RLL (relative lesion length) 48% and RFC (radial fungal colonization) 40% when compared to those supplied with the higher rate (240 mg de K dm -3 ). Consequently, substantial declines in stomatal conductance (g s ), in line with reductions in internal-to-ambient CO 2 concentration ratio (C i /C a ) and absence of detectable changes in the chlorophyll a fluorescence parameters, suggest that the reduction on the net carbon assimilation rate (A) of those plants are, at least initially, due to stomatal limitations. High concentrations of potassium, calcium and manganese were found in the stem tissues of plants inoculated and supplied with the highest concentration of K, most likely involved in the local development of defense mechanisms which possibly hold a higher resistance against pathogen’s spread. The results of this study suggest that the supply of K favors the resistance of plants, because the plants that received the higher dose of K showed less severity, leading to better photosynthetic performance.